ANALISIS SISTEM ANTRIAN PADA BENGKEL PT. GLOBAL JAYA PERKASA PEKANBARU - Fatimah Maharani Siregar; Samsir '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Queuing problem is a problem that is always found, almost all activities undertaken related to the issue queue. So was what happened in the workshop PT. Global Jaya Perkasa Pekanbaru, always be a queue of customers who want to serve. This study was conducted to determine the optimalization of queuing system, the number of customers in the queue, the number of customers in the system, the time spent in the queue of customers, the time spent in the system customers, and queuing system utilization in the workshop PT. Global Jaya Perkasa Pekanbaru. Here queuing system that applies a multi –channel model of single phase (M/M/S). Where there is a path queue of customers to be served by two or more service facilities (mechanical). With the queue discipline is Fisrt Come Firts Serve (FCFS). From the research, that customers come average as many 122 people, while the number of mechanical who serve an average of 4 people. From this state gained a number of customers waiting in queue is 7 people with an average waiting time in the queue is 24 minutes. The number of customers waiting in the system as many as 11 people with an average waiting time for 36 minutes, and the queuing system utilization by 0,01%. While the mechanics are available by 5 people, only available mechanics do not operate simultaneously.Keywords : queuing system, multi channel single phase (M/M/S), operations management, and first come first serve (FCFS).